2018
DOI: 10.1159/000492516
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Deletion of 5q22.2q23.1 Including APC and TSSK1B in a Patient with Adenomatous Polyposis and Asthenoteratozoospermia

Abstract: Interstitial 5q22 deletions are relatively rare and usually represented by severe clinical features such as developmental delay and growth retardation. Here, we report a 23-year-old male patient, referred to our laboratory for genetic confirmation of possible familial adenomatous polyposis. MLPA and the subsequent array CGH identified an approximately 8-Mb-sized deletion in the 5q22.2q23.1 locus. Further analysis of the deleted region and the genes within suggested a possible role for the TSSK1B (testis-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…This finding was explained by other research on the cattle-yak; that is, such a phenomenon may be due to the germ-cell apoptosis being initiated at the pachytene stage and the meiosis being blocked [33]. This phenomenon was also observed in a medical case in which a patient with a heterozygous deletion in 5q22.2q23.1 (including TSSK1B) suffered from asthenoteratozoospermia, with cephalic defects, numerous atypical sperm morphologies, and low sperm motility, thus demonstrating that TSSK1B regulates spermatozoan development and quality [34]. Other studies on the transcriptome of gonad and gametogenesis demonstrated that the TSSK1like gene is vital to male gonadal development and spermatogenesis [35,36].…”
Section: Discussionmentioning
confidence: 71%
“…This finding was explained by other research on the cattle-yak; that is, such a phenomenon may be due to the germ-cell apoptosis being initiated at the pachytene stage and the meiosis being blocked [33]. This phenomenon was also observed in a medical case in which a patient with a heterozygous deletion in 5q22.2q23.1 (including TSSK1B) suffered from asthenoteratozoospermia, with cephalic defects, numerous atypical sperm morphologies, and low sperm motility, thus demonstrating that TSSK1B regulates spermatozoan development and quality [34]. Other studies on the transcriptome of gonad and gametogenesis demonstrated that the TSSK1like gene is vital to male gonadal development and spermatogenesis [35,36].…”
Section: Discussionmentioning
confidence: 71%
“…Deletion of tssk1b gene was detected in a patient with asthenoteratozoospermia, and further analysis of the AZF region on the Y-chromosome showed no microdeletion, suggesting that tssk1b is important for male fertility 97 . These findings indicate that TSSK1B is important for spermatogonial development, cell differentiation, spermiogenesis, and spermiation.…”
Section: Resultsmentioning
confidence: 94%
“…It is likely that the many other genes located in the deleted regions also play a role in these predisposition manifestations and mental retardation [39]. A patient with a 5q22.2q23.1 deletion with FAP but without mental retardation or dysmorphic features was reported [37]. This finding was attributed to the small size of the deleted region relative to previously reported cases, harboring fewer genes.…”
Section: Apc-associated Familial Polyposis (Fap)mentioning
confidence: 87%
“…Currently, about 20 cases have been reported in the literature. In only 4 was the exact deletion site identified by chromosomal microarray (CMA) testing [36,37]. According to one group, deletions encompassing the distal portion of the region, from 5q22 to 5q31.1, may lead to a more severe phenotype with severe mental retardation and hypotonia, whereas the absence of the proximal portion, from 5q15 to 5q22.2, is associated with mild mental retardation, minor dysmorphic features, and possible organ abnormalities such as horseshoe kidneys [38].…”
Section: Apc-associated Familial Polyposis (Fap)mentioning
confidence: 99%